Memória e imaginário rural: construção de narrativas e produção refletida em artes visuais no ensino rural - Schutz, Júlia Andressa (2020)
This dissertation is linked to the research line LP2 - School Practices and Public Policies, of the Postgraduate Program in Education at the Federal University of Santa Maria (UFSM), on the theme “Rural Memory and Imaginary: Construction of Narratives and Reflected Production in Visual Arts in rural education ”. The research problem seeks to answer the following question: to what extent Reflected Production - from plastic work and using Narratives, can bring up Memory, Imaginary and Life history of students in a rural context, and what how this rural environment reverberates on the students life and in myself, as a teacher. Therefore, its general objective is to understand how this Reflected Production can bring out the elements of Memory, Imaginary and Life History of the students in a rural school through plastic work and the construction of Narratives, as well as how this reflection links to the rural context, and how this context is perceived in students life and in myself, as a teacher. As a theoretical contribution, authors were used, such as: Josso (2010), Delory-Momberger (2006), Passeggi (2016), anchored in (Auto) Biographical research; Souza (2007), to understand Ruralities; Dewey (2010), about art as experience and Reflected Production. This theme is justified by its original character, namely: approaching a classroom in a rural school, issues related to Visual Arts and the concepts of Memory, Imaginary, Ruralities, Reflected Production. The methodology is based on qualitative research, which uses the approach anchored in the (Auto) Biographical Narratives. As data production tools, workshops were held; the technique for data production made use of Reflected Production, a scheme created to account for the reflection of the work, as well as the use of field diaries. The research was carried out in a rural school in the interior of the municipality of Agudo/RS. The school is related to the author's educational experiences. The research was carried out in two classes, 7th and 9th years, through a period of insertion in the school and with the classes for an approximation between the researcher and the students. Finally, I develop the research, showing how the Art workshops were developed, as well as the data collection, using the (Auto) Biographical Narratives and the plastic works of the students in a rural school as an analysis.